Functioning and health in patients with cancer on home-parenteral nutrition: a qualitative study - Mueller, Martin (BioMed Central, 2010)
BACKGROUND: Malnutrition is a common problem in patients with cancer. One possible strategy to prevent malnutrition and further deterioration is to administer home-parenteral nutrition (HPN). While the effect on survival is still not clear, HPN presumably improves functioning and quality of life. Thus, patients' experiences concerning functioning and quality of life need to be considered when deciding on the provision of HPN. Currently used quality of life measures hardly reflect patients' perspectives and experiences. The objective of our study was to investigate the perspectives of patients with cancer on their experience of functioning and health in relation to HPN in order to get an item pool to develop a comprehensive measure to assess the impact of HPN in this population. METHODS: We conducted a series of qualitative semi-structured interviews. The interviews were analysed to identify categories of the International Classification of Functioning, Disability and Health (ICF) addressed by patients' statements. Patients were consecutively included in the study until an additional patient did not yield any new information. RESULTS: We extracted 94 different ICF-categories from 16 interviews representing patient-relevant aspects of functioning and health (32 categories from the ICF component 'Body Functions', 10 from 'Body Structures', 32 from 'Activities & Participation', 18 from 'Environmental Factors'). About 8% of the concepts derived from the interviews could not be linked to specific ICF categories because they were either too general, disease-specific or pertained to 'Personal Factors'. Patients referred to 22 different aspects of functioning improving due to HPN; mainly activities of daily living, mobility, sleep and emotional functions. CONCLUSIONS: The ICF proved to be a satisfactory framework to standardize the response of patients with cancer on HPN. For most aspects reported by the patients, a matching concept and ICF category could be found. The development of categories of the component 'Personal Factors' should be promoted to close the existing gap when analyzing interviews using the ICF. The identification and standardization of concepts derived from individual interviews was the first step towards creating new measures based on patients' preferences and experiences which both catch the most relevant aspects of functioning and are sensitive enough to monitor change associated to an intervention such as HPN in a vulnerable population with cancer.